The effect of end condition on spine segment biomechanics in compression with lateral eccentricity. (9th November 2021) - Melnyk, Angela; Whyte, Tom; Van Toen, Carolyn; Yamamoto, Shun; Street, John; Oxland, Thomas R.; Cripton, Peter A.
Abstract: During axial impact compression of the cervical spine, injury outcome is highly dependent on initial posture of the spine and the orientation, frictional properties and stiffness of the impact surface. These properties influence the "end condition" the spine experiences in real-world impacts. The effect of end condition on compression and sagittal plane bending in laboratory experiments is well-documented. The spine is able to escape injury in an unconstrained flexion-inducing end condition (e.g. against an angled, low friction surface), but when the end condition is constrained (e.g. head pocketing into a deformable surface) the following torso can compress the aligned spine causing injury. The aim of this study was to determine whether this effect exists under combined axial compression and lateral bending. Over two experimental studies, twenty-four human three vertebra functional spinal units were subjected to controlled dynamic axial compression at two levels of laterally eccentric force and in two end conditions. One end condition allowed the superior spine to laterally rotate and translate (T-Free) and the other end condition allowed only lateral rotation (T-Fixed). Spine kinetics, kinematics, injuries and occlusion of the spinal canal were measured during impact and pre- and post-impact flexibility. In contrast to typical spine responses in flexion-compression loading, the cervical spine specimens in this study did not escape injury in lateral bending when allowed to translate laterally. The specimen group that allowed lateral translation during compression had more injuries at high laterally eccentric force, saw greater peak canal occlusions and post-impact flexibility than constrained specimens.